SCFβ-TRCP E3 ubiquitin ligase targets the tumor suppressor ZNRF3 for ubiquitination and degradation. Issue 10 (1st March 2018) - Ci, Yanpeng; Li, Xiaoning; Chen, Maorong; Zhong, Jiateng; North, Brian J; Inuzuka, Hiroyuki; He, Xi; Li, Yu; Guo, Jianping; Dai, Xiangpeng
Abstract: Wnt signaling has emerged as a major regulator of tissue development by governing the self-renewal and maintenance of stem cells in most tissue types. As a key upstream regulator of the Wnt pathway, the transmembrane E3 ligase ZNRF3 has recently been established to play a role in negative regulation of Wnt signaling by targeting Frizzled (FZD) receptor for ubiquitination and degradation. However, the upstream regulation of ZNRF3, in particular the turnover of ZNRF3, is still unclear. Here we report that ZNRF3 is accumulated in the presence of proteasome inhibitor treatment independent of its E3-ubiquitin ligase activity. Furthermore, the Cullin 1-specific SCF complex containing β-TRCP has been identified to directly interact with and ubiquitinate ZNRF3 thereby regulating its protein stability. Similar with the degradation of β-catenin by β-TRCP, ZNRF3 is ubiquitinated by β-TRCP in both CKI-phosphorylation- and degron-dependent manners. Thus, our findings not only identify a novel substrate for β-TRCP oncogenic regulation, but also highlight the dual regulation of Wnt signaling by β-TRCP in a context-dependent manner where β-TRCP negatively regulates Wnt signaling by targeting β-catenin, and positively regulates Wnt signaling by targeting ZNRF3.